Influence of selected alloying variations on liquid metal embrittlement susceptibility of quenched and partitioned steels. (December 2022) - Bhattacharya, D.; Cho, L.; Colburn, J.; Smith, D.; Marshall, D.; van der Aa, E.; Pichler, A.; Ghassemi-Armaki, H.; Pottore, N.; Findley, K.O.; Speer, J.G.
Graphical abstract: Highlights: Si aggravates liquid metal embrittlement sensitivity of advanced high strength Q&P steels. Si influences the susceptibility to liquid metal embrittlement more strongly than C, Mn, or Al. Si slows down Fe-Zn intermetallic formation and promotes a "direct" contact between liquid Zn and the steel substrate. The Si effect on retarded Fe-Zn alloying is consistent with the phase equilibria of the Fe-Zn-Si ternary system. Abstract: In this work, the influence of selected alloying variations on Zn-assisted liquid metal embrittlement (LME) susceptibility of Zn-coated advanced high strength steels (AHSS) is investigated. Cold-rolled AHSS alloys of different carbon (C), manganese (Mn), silicon (Si), and aluminum (Al) concentrations were continuous-annealed to generate a third generation AHSS microstructure (composed of martensite and retained austenite) via quenching and partitioning. High temperature tension tests using simulated spot-weld thermomechanical cycles revealed no significant influence of C and Mn variations on the Zn-LME susceptibility of AHSS. On the other hand, Zn-LME susceptibility was strongly correlated with the Si content of AHSS. A direct comparison of the (reacted) coating microstructures of the Si-alloyed and Low-Si AHSS variants revealed that Si in the AHSS substrate suppresses Fe–Zn alloying reactions and retards the nucleation and growth of Fe-Zn intermetallic phases at the coating-substrate interface in these spot weld simulations. The suppressed intermetallic formation at elevated Si concentrations is consistent with phase equilibria considerations in the Fe-Zn-Si ternary system. In the context of Zn-assisted LME, therefore, Si is hypothesized to aggravate LME behavior by increasing the liquid Zn availability for embrittlement and promoting direct contact between liquid Zn and the AHSS steel substrate.